Stearate‐to‐palmitate ratio modulates endoplasmic reticulum stress and cell apoptosis in non‐B non‐C hepatoma cells. Issue 4 (6th March 2018) - Shibasaki, Yasushi; Horikawa, Makoto; Ikegami, Koji; Kiuchi, Ryota; Takeda, Makoto; Hiraide, Takanori; Morita, Yoshifumi; Konno, Hiroyuki; Takeuchi, Hiroya; Setou, Mitsutoshi; Sakaguchi, Takanori
Abstract : The increased prevalence of hepatocellular carcinoma (HCC) without viral infection, namely, NHCC, is a major public health issue worldwide. NHCC is frequently derived from non‐alcoholic fatty liver (NAFL) and non‐alcoholic steatohepatitis, which exhibit dysregulated fatty acid (FA) metabolism. This raises the possibility that NHCC evolves intracellular machineries to adapt to dysregulated FA metabolism. We herein aim to identify NHCC‐specifically altered FA and key molecules to achieve the adaptation. To analyze FA, imaging mass spectrometry (IMS) was performed on 15 HCC specimens. The composition of saturated FA (SFA) in NHCC was altered from that in typical HCC. The stearate‐to‐palmitate ratio (SPR) was significantly increased in NHCC. Associated with the SPR increase, the ELOVL6 protein level was upregulated in NHCC. The knockdown of ELOVL6 reduced SPR, and enhanced endoplasmic reticulum stress, inducing apoptosis of Huh7 and HepG2 cells. In conclusion, NHCC appears to adapt to an FA‐rich environment by modulating SPR through ELOVL6. Abstract : Saturated fatty acid composition was different in between cancerous and non‐cancerous regions of hepatocellular carcinoma without viral infections (NHCC). In the cancerous region of NHCC, stearate‐to‐palmitate ratio (SPR) increased in concomitant with ELOVL6 protein expression. ELOVL6 gene silencing decreased SPR, induced endoplasmic reticulum stress and led to cellular apoptosis in Huh7 and HepG2 cells.